Profile of Student’s Creative Thinking Ability in Senior High School on Climate Change Materials - Susanti, Fajaria Meli; Apridiana Lestari, Nurita (International Journal of Research and Community Empowerment, 2023)
Climate change is a global problem that is happening right now. An increase in the temperature of the earth's surface causes an ecosystem imbalance because it endangers living thing. This study aims to analyze the profile of students' creative thinking abilities at SMAN 3 Jombang on climate change material. The method of research is quantitative descriptive. The sample used in this study was class XI students at SMA Negeri 3 Jombang, totaling 66 students. The instruments used in this study were 4 essay questions which had been validated by three expert lecturers and declared valid. The instrument used includes indicators of creative thinking, namely fluency, flexibility, elaboration, and originality. Based on the results of the analysis of creative thinking abilities, the fluency indicator obtained a percentage of 29%, flexibility of 20%, elaboration of 31%, and originality of 29%. It can be concluded, overall, the percentage of creative thinking ability is 27.46%. This shows that the students' creative thinking abilities at SMA Negeri 3 Jombang are still relatively low, so there is a need for learning that can improve creative thinking abilities.